Kurikulum Pendidikan Agama Islam Indonesian untuk Anak Usia Dini: Indonesian Islamic Religious Education Curriculum for Early Childhood - Rahayu, Watik; Formen, Ali; Isdaryanti, Barokah (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
The purpose of this study was to determine the curriculum of Islamic religious education for Early Childhood. This study was conducted using the Systematic Literature Review (SLR) method. The articles used were sourced from the Sinta database assisted by Connected Papers with a span of 2015-2024. The results of the study indicate that the curriculum of Islamic religious education for early childhood in its concept emphasizes thematic, integral-holistic and oriented curriculum on daily life and is centered on students. The curriculum material includes an introduction to the Creator and His creation, ablution, reading Asma'ul Husna, reading daily prayers and morals. The learning method is based on science and thematics that unite beliefs, worship, and morals as well as the habituation of worship practices and the practice of reading the Qur'an through the Iqra' method.   ABSTRAK  Tujuan dari penelitian ini adalah untuk mengetahui kurikulum pendidikan agama Islam untuk Anak Usia Dini. Penelitian ini dilakukan dengan menggunakan metode Systematic Literature Review (SLR). Artikel yang digunakan bersumber dari database Sinta yang dibantu oleh Connected Papers dengan rentang 2015-2024. Hasil penelitian menunjukkan bahwa kurikulum PAI anak usia dini dalam konsepnya menekankan kurikulum tematik, integral-holistik dan berorientasi pada kehidupan sehari-hari serta berpusat pada siswa. Materi kurikulum meliputi pengantar Sang Pencipta dan ciptaan-Nya, wudhu, membaca Asma'ul Husna, membaca doa sehari-hari dan akhlak. Metode pembelajaran berbasis ilmiah dan tematik yang menyatukan keyakinan, ibadah, dan moral serta pembiasaan praktik ibadah dan praktik membaca Al-Qur'an melalui metode Iqra'.